Modification of coir fiber as polymer reinforcement - Mohd Aizuddin, Ab Razak (2010)
Studies on the use of natural fibers as replacement to man-made fiber in fiber-reinforced composites have increased and opened up further industrial possibilities. This research will enhance the usage of composite in industrial application and also in household product.The objectives of this research are to modify the surface property of coir fiber and to study the bonding mechanism between the coir fiber and the polymer.In order to achieve the objective, there are several steps have been done during the research that is the surface treatment of fiber by NaOH solution with manipulated concentration, composites production with epoxy resin and coir fiber as the reinforcement and also the characterization of the composites.The process flows of this research are the fiber preparation,stock solution preparation, fiber treatment, fiber testing,polymer preparation,and polymer testing. From the result,untreated coir fiber has Kappa number of 46.75,20% NaOH treated fiber has Kappa number of 32.63, 25% NaOH treated fiber has Kappa number of 28.86, and 30% NaOH treated fiber has Kappa number of 20.09.The treatment have made the fiber more thermal resistant as approved by the increase in the decomposition temperature of coir fiber and also increase in weight percent remaining at specific temperature that is at 300°C.For untreated fiber,it have decomposition temperature of 336.64°C while for 20%NaOH treated fiber, the decomposition temperature is 366.13°C.From the results also, increasing in NaOH concentration has result in increasing tensile strength of the composite and the optimum concentration for the highest tensile strength is at 25% NaOH treated fiber. The conclusion that have been made is the alkali treatment have been successfully done and renewable fibers like coir can be used as reinforcing materials for low cost composites,due to the economic and environmental advantages of such materials.